Analisis Pengaruh Kecerdasan Buatan Pada Pengalaman Belanja Konsumen Di Platform E-Commerce Indonesia - Andromeda (CV. SINAR HOWUHOWU, 2025)
The development of artificial intelligence (AI) has significantly enhanced the quality of services offered by e-commerce platforms in Indonesia. This study aims to analyze the influence of AI implementation on consumer shopping experiences, particularly in terms of personalization, usability, service speed, and overall satisfaction. The research employs a literature-based and descriptive approach to identify the relationship between AI-driven features and consumer behavior. The findings indicate that AI technologies such as recommendation systems, chatbots, and visual search positively influence consumers’ perceptions of convenience and shopping efficiency. However, the study also highlights challenges related to data privacy and algorithmic bias, which may affect user trust. Overall, the implementation of AI is proven to be a critical factor in creating more personalized, adaptive, and effective shopping experiences on Indonesian e-commerce platforms.